Effect of KATP channel blocker glibenclamide on PACAP38-induced headache and hemodynamic. (August 2022) - Kokoti, Lili; Al-Karagholi, Mohammad Al-Mahdi; Elbahi, Fatima Azzahra; Coskun, Hande; Ghanizada, Hashmat; Amin, Faisal Mohammad; Ashina, Messoud
Objective: To determine whether glibenclamide, a non-selective adenosine 5′-triphosphate-sensitive K + (KATP ) channel blocker, attenuates pituitary adenylate cyclase-activating polypeptide-38 (PACAP38)-induced headache and vascular changes in healthy volunteers. Methods: In a double-blind, randomized, placebo controlled and crossover design, 22 healthy volunteers were assigned to receive an intravenous infusion of 10 picomole/kg/min pituitary adenylate cyclase-activating polypeptide-38 over 20 minutes followed by oral administration of 10 mg glibenclamide or placebo. The primary endpoint was the difference in incidence of headache (0–12 hours) between glibenclamide and placebo. The secondary endpoints were a difference in area under the curve for headache intensity scores, middle cerebral artery velocity (VmeanMCA ), superficial temporal artery diameter, radial artery diameter, heart rate, mean arterial blood pressure and facial skin blood flow between the two study days. Results: Twenty participants completed the study. We found no difference in the incidence of pituitary adenylate cyclase-activating polypeptide-38-induced headache after glibenclamide (19/20, 95%) compared to placebo (18/20, 90%) ( P  = 0.698). The area under the curve for headache intensity, middle cerebral artery velocity, superficial temporal artery diameter, radial artery diameter, facial skin blood flow, heart rate and mean arterial blood pressure did not differ between pituitary adenylate cyclase-activating polypeptide-38-glibenclamide day compared to pituitary adenylate cyclase-activating polypeptide-38-placebo day ( P  > 0.05). Conclusions: Posttreatment with 5′-triphosphate-sensitive K+ channel inhibitor glibenclamide did not attenuate pituitary adenylate cyclase-activating polypeptide-38-induced headache and hemodynamic changes in healthy volunteers. We suggest that pituitary adenylate cyclase-activating polypeptide-38-triggered signaling pathway could be mediated by specific isoforms of sulfonylurea receptor subunits of 5′-triphosphate-sensitive K+ channels and other types of potassium channels.